Metacognition Analysis of Students' Problem-Posing Process for Group Homomorphism Material - Nugraheni, Liknin; Ladyawati, Erlin; Maftuh, Moh Syukron (Jurnal Amal Pendidikan, 2024)
Group homomorphism, a complex topic in the Algebra Structure 1 course at Universitas PGRI Adi Buana Surabaya, requires high-level thinking, creativity, and the integration of ideas. Metacognition plays an important role in helping students have the problem-posing process, which includes understanding, translating, editing, and selecting information. This study aimed to analyze the metacognitive processes of students with low and high abilities in creating problems related to group homomorphism. The findings show that 83.33% of low-ability students operate at the tacit use level, where they do not consciously consider their decisions or thinking processes. In contrast, high-ability students obtained 100% of the reflective use level during the planning and monitoring stages, meaning that they have reflected thought processes before, during, and after problem-posing, while also identifying improvements and next steps. Furthermore, 100% of high-ability students achieve the strategic use level in the evaluation stage, showing their ability to consciously regulate their thought processes and apply targeted strategies to improve the accuracy of their evaluations when creating problems related to group homomorphism.